2006
DOI: 10.1007/s00383-006-1709-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal approach to prophylaxis of necrotizing enterocolitis: clinical report and review of literature

Abstract: For the first time a multimodal approach to NEC prophylaxis is reported, consisting of early trophic feeding with human breast milk, and enteral administration of an antibiotic, an antifungal agent, and probiotics. A retrospective analysis of local protocol of NEC prophylaxis is presented. Included were all VLBWI admitted to the NICU, including transfers within the first 28 days of life. These infants were divided into two groups, an "inborn group" (infants admitted within the first 24 h of life) and an "outbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 80 publications
(89 reference statements)
1
35
0
Order By: Relevance
“…In a retrospective analysis Schmolzer et al [30] found a statistically significant decreased risk of NEC in the group receiving early NEC prophylaxis (e.g. antibiotics, probiotics).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis Schmolzer et al [30] found a statistically significant decreased risk of NEC in the group receiving early NEC prophylaxis (e.g. antibiotics, probiotics).…”
Section: Discussionmentioning
confidence: 99%
“…Our longlasting experience in the use of enteral gentamycin has revealed neither a change in ESBL producing enterobacteria in stool surveillance cultures nor in antimicrobial sensitivity patterns (22). This is also the case for the use of LCR resulting in very low NEC rates as compared to other studies (16).…”
Section: Discussionmentioning
confidence: 89%
“…As far as our prophylactic multimodal, anti-infective regimen resulted in very low NEC rates (16) we felt that a placebo controlled trial might be unethical. Hence, we compared our complication rates to the published evidence in term critically ill neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations